Preliminary Phytochemical Investigation and Antibacterial Activity Identification of Stems of Calotropis procera Plant in Iraq by GC. MS - Estabraq H. Naser (Journal of Global Pharma Technology, 2016)
Calotropis procera is a plant from Asclepiadaceae family. The preliminary phytochemical investigation of C. procera stems exhibit its high contents of flavonoids, alkaloids, saponins, while terpenoids, and reducing sugar are in lower percent. Its previously used in treatment of many diseases such as cough, bronchitis, ascites, asthma, eczema, leprosy, cutaneous diseases, and intestinal worms. GC. MS analysis of stems ethanolic extract showed that the highest percent in 100% ethanolic stems extract belongs to Octadecanoic acid 20.33%, Hexa-hydro-farnesol 6.16%, and Linolenic acid ethyl ester 39.59 while the highest percent in 70% ethanolic stems extract belongs to (-)-Vincadifformine 17.13%, Dodecanoic acid 13.97%, Methyl arachidonate 9.01%, and (+)-α-Tocopherol 6.66%. The others chemical compounds percent range from about 5%-0.3%. The antibacterial activity of stems of Calotropis procera plant compared with streptomycin as standard antibiotic against four different types of bacteria revealed that the ethanolic extracts have no effect on Escherichia coli, and Pseudomonas sp. While these extracts have ability to kill Staphylococcus aureus, and Basillus subtilis bacteria which are more sensitive.Keywords: Usher, GC. MS, Calotropis Procera, phytochemical, Sodom apple, Antibacterial.